Cavitation-induced droplet fragmentation in focused ultrasonic fields - Olga Kudryashova; Andrey Shalunov; Vladimir Khmelev; Sergey Terentiev; Alexander Sinkin (Ultrasonics Sonochemistry)
Liquid spraying is widely used in industry, medicine, ecology, etc. At the same time, there is significant interest in highly dispersed aerosols, and there are cases where it is necessary to increase the dispersity of liquid droplets in a non-contact manner and/or droplets already suspended in the air. Ultrasound is used to enhance the dispersity of substances, such as powder particles in a liquid or for homogenizing suspensions. However, when applied to aerosols, ultrasound is typically used for particle coagulation and precipitation. This is because breaking up droplets suspended in air requires higher power input. For the first time, we investigate the processes of cavitation-induced acoustic droplet dispersion using novel ultrasound sources. The development of ultrasonic droplet fragmentation methods will expand the technological applications of aerosols, including for air and surface disinfection in enclosed spaces. Theoretically and experimentally, we determined the critical conditions for cavitation-induced droplet fragmentation. We identified the lower threshold and the saturation threshold for such fragmentation, as well as the induction time, degree of droplet deformation, dispersity, and the minimum size of newly formed droplets resulting from fragmentation. This work demonstrates significant potential for sanitation measures conducted in compliance with safety requirements, thereby contributing to the preservation and improvement of public health worldwide.